Sustainable smart irrigation system (SIS) using solar PV with rainwater harvesting technique for indoor plants - Islam, Syed Zahurul; Kamarudin, Muhammad Saufi; Abdullah, Mohd Noor; Mohaffyza, Mimi; Sern, Lai Chee; Othman, Mohammad Lutfi; Uddin, Jasim (Public Library of Science, 2025)
The project aims to develop a sustainable smart irrigation system (SIS) for the indoor plant irrigation by integrating photovoltaic (PV), internet of things (IoT), and rainwater harvesting techniques. The addressed problem involves the inconsistency and tediousness of manual watering, emphasizing the need for a sustainable design for a SIS. The IoT system consists of soil moisture sensor with GSM module powered by PV and an algorithm was developed to adjust irrigation schedules based on soil moisture data. The objectives of this project are to design and optimize the PV-powered irrigation system and implement an Arduino-enabled automatic system with SMS-triggered functionality. The methodology involves system modelling for water requirements and sizing of PV, battery, pump, and MPPT based on the load demand. The rainwater harvesting structure designed ensures water sustainability for plants’ irrigation. The system is then implemented using moisture and ultrasonic sensors managed by Arduino Uno embedded system. The electrical performance of the PV was analyzed on both cloudy and moderately luminous days, with irradiance ranging from 250.4 to 667.8 and 285.5 to 928 W/m2, respectively. The average output voltage and current of the battery were observed to be 13.04 V and 0.37 A (cloudy), and 13.45 V and 0.47 A (moderate) days, respectively. The rainwater collection test revealed more than 36 L in the tank after one week, indicating it could sustain watering the three plants for 72 days. Based on the analysis, the project can save 14.97 kgCO2 emissions per year compared to the current emissions released into the environment. The overall cost of the system is approximately RM670 (US$139.50). The SIS aligns with SDG 7, promoting affordable and integrates with 12th Malaysia Plan for more efficient and environmentally friendly agricultural and water management practices.